Motor-Less Robotic Gripper: Driving Mechanism by Robotic Manipulator Movement - Toshihiro Nishimura; Kosei Ueno; Tetsuyou Watanabe (IEEE Access)
This paper proposes a novel robotic gripper capable of antipodal grasping without requiring motors in its structure. The developed gripper generates grasping motion through the rotation of the manipulator’s terminal joint while maintaining its rotational capability for posturing. The key feature is a self-motion switching mechanism that automatically switches between finger motion and gripper’s orientation based on the tip force applied to the fingers. When the tip force is below a threshold value, the mechanism generates finger opening/closing motion; when the force exceeds the threshold, it activates the gripper’s orientation. This enables the robotic system to perform standard object manipulation tasks, including grasping, transferring with posture adjustment, and placing, without the installation of a motor. A special control strategy is developed to determine the manipulator motion for achieving the desired gripper motion during object manipulation. The developed gripper is evaluated experimentally, demonstrating that the gripper achieves a maximum closing speed of 165.9 mm/s and a grasping force of 28.5 N with 3D-printed components. The motor-less structure eliminates the need for cable installation and electrical settings in the gripper, contributing to system simplification. The effectiveness of the gripper is experimentally validated through various pick-and-place operation tests.